Apropriações tecnológicas em segmentos musicais periféricos: o caso do rock independente de Teresina - Thiago Meneses Alves (Ciências Sociais Unisinos)
The general goal of this article is to analyze the implications of recent changes in the music culture for the independent musical contexts based far from the main political, economic, and media centers, from a research about the independent rock in Teresina, capital of the Brazilian state of Piauí. More specifically, our goal is to discuss the role of technological appropriations in the increase of the production in this kind of artistic-musical context. The main argument is that the independent rock of Teresina has reached a relative stage of specificity and autonomy thanks to the opportunities open for the technologies of information and communication, which provides the conditions to the construction of a big catalog of works. However, the permanence of old problems, linked to financial sustainability, as well as the emergence of new obstacles, linked to the visibility of this kind of production in an abundant and super segmented cultural market, still configure some of the big challenges to be surpassed.